Role of Bank Specific, Macroeconomic and Risk Determinants of Banks Profitability: Empirical Evidence from Ghana's Rural Banking Industry. - Boadi, Eric Kofi; Li, Yao; Lartey, Victor Curtis (International Journal of Economics and Financial Issues, 2016)
This paper analyzes bank specific, macroeconomic and some risk determinants of bank profitability of Rural and Community Banks (RCBs) in Ghana. Fixed effect panel regression analysis is applied on 114 RCBs annual financial reports during the period 2005-2013. The results generally suggests that capital adequacy, asset quality, liquidity management, investment, gross domestic product growth rate, inflation, funding risk and bank resilience risk are significant determinants of RCBs profitability though with varying degrees. Whereas management efficiency, and bank size cannot be considered as positive contributors to RCBs profitability. The study also indicates that continuous profitability performance of RCBs can curtail shortfall in funding risk and enhance RCBs stability. Keywords: Bank Performance, Bank Specific Determinants, Macroeconomic Factors, Risk Factors JEL Classifications: C5, E4, G2, G21